A Study on Customers Preference Towards Digital Banking in Modernity - Kavya J Aisha; Ramya Rakesh (PT FORMOSA CENDEKIA GLOBAL, 2022)
Banking sector is indispensable in our routine life, as it encourages the customers to ameliorate themselves in the digital world. Here the customers include the general public, the Government, Merchandiser and the Entrepreneur which helps them (Customers) to access the digital world instantly. It helps the society to move from traditional banking to digital banking which makes the work a little more attainable. It is observed that the banking sector has thrived into the digital world. This paper concentrates on the innumerable scope in the upcoming digitalized world. The core focus of this study is Customers' perception towards Digital Banking in Modernity.